Using novel methodologies to examine the impact of artificial light at night on the cortisol stress response in dispersing Atlantic salmon (Salmo salar L.) fry. (8th December 2015) - Newman, Rhian C.; Ellis, Tim; Davison, Phil I.; Ives, Mark J.; Thomas, Rob J.; Griffiths, Sian W.; Riley, William D.
Abstract : Artificial light at night (ALAN) is known to disrupt the nocturnal dispersal behaviour of Atlantic salmon fry, yet the underlying physiological mechanism is unknown. Here novel methodologies are utilised to examine whether behavioural disruption seen in dispersing fry is mediated via a cortisol stress response. Fry showed the capacity to mount a stress response, however, the two methods for sampling cortisol provide conflicting results as to whether ALAN acts as a stressor to dispersing fry. Abstract : Artificial light at night (ALAN) is gaining recognition as having an important anthropogenic impact on the environment, yet the behavioural and physiological impacts of this stressor are largely unknown. This dearth of information is particularly true for freshwater ecosystems, which are already heavily impacted by anthropogenic pressures. Atlantic salmon ( Salmo salar L.) is a species of conservation and economic importance whose ecology and behaviour is well studied, making it an ideal model species. Recent investigations have demonstrated that salmon show disrupted behaviour in response to artificial light; however, it is not yet clear which physiological processes are behind the observed behavioural modifications. Here, two novel non-invasive sampling methods were used to examine the cortisol stress response of dispersing salmon fry under different artificial lighting intensities. Fish egg and embryos were reared under differing ALAN intensities and individual measures of stress were subsequently taken from dispersing fry using static sampling, whereas population-level measures were achieved using deployed passive samplers. Dispersing fry exposed to experimental confinement showed elevated cortisol levels, indicating the capacity to mount a stress response at this early stage in ontogenesis. However, only one of the two methods for sampling cortisol used in this study indicated that ALAN may act as a stressor to dispersing salmon fry. As such, a cortisol-mediated response to light was not strongly supported. Furthermore, the efficacy of the two non-invasive methodologies used in this study is, subject to further validation, indicative of them proving useful in future ecological studies.